Challenges of architectural, urban and landscape design within the new economic models - Chaverri-Flores, Laura (2020)
In our contemporary capitalist society, there is a tendency to self-destruction backed by human domination over nature. National parks, cities and architecture have become objects of consumption. The objective of this work is to identify consequences, challenges and alternatives for urban, landscape and architectural design in the neoliberal economic system. Regarding the methodology, different bibliographic reviews were carried out considering authors from various disciplines such as economics, geography, and architecture, particularly certain works by Franz Hinkelammert, who compares capitalism with a new market religion that leads to selfdestruction. In addition, the argumentation is exemplified with some specific case studies and a dialogue and reflection is generated around the impact that the neoliberal economic system has had on the city and the landscape, where private property is above public space. An analysis is performed on the shopping malls that symbolize the new temples of the neoliberal religion. Within the results and discussion, the consequences are compiled, but old forgotten paradigms are explored as alternatives, as well as the possibility of using design as a common good. Some of the final conclusions reveal the dependence of design on the designer’s way of thinking, who could generate innovations. Some resistance to the prevailing system such as resilient architecture is reviewed, and the urgency of a paradigm shift in today’s society is evidentiated.